Survey pendidikan olahraga pada Sekolah Menengah di Kabupaten Pinrang - Herman H; Arifuddin Usman (Seminar Nasional LP2M UNM, 2019)
This research is a type of descriptive analysis research that uses quantitative research design. This study aims to determine the Facilities and Infrastructure of SMA / SMK in Pinrang Regency viewed from Factors; (1) Ownership Status (2) Completeness, and (3) Feasibility. The population is 21 High School / State Vocational Schools in Pinrang Regency. The sample used was 12 SMA / Vocational High Schools in Pinrang Regency. The data analysis technique used is descriptive analysis, frequency, using SPSS 2017. The results of the study indicate that; facilities and infrastructure for physical and sports education in high schools / state vocational schools in Pinrang Regency both in terms of ownership status, completeness and feasibility on average are in a fairly good category, there are 1 high school / state vocational high school that are included in the category of Good with a percentage of 8.3%, and 11 Public High Schools / Vocational Schools are in the Pretty Good category with a percentage of 91.7%.